Architectural and construction drawings and geometric dimensions of the mausoleum of Khoja Ahmed Yasawi - Baidabekov Әуез; Kemelbekov Эльмира (Рroblems of engineering and professional education, 2022)
This article is about an amazing multifunctional building built in the Middle Ages, built in a modern style that has no analogues in Central Asia, and has become the center of the days. The mausoleum of Khoja Ahmed Yasawi is a grandiose architectural structure of the Middle Ages, built for the purpose of reconstruction and by order of Emir Temur after the victory in the long war. The building consists of two floors, six corridors separating twenty-three rooms and eight main rooms, and two corridors for exiting the main portal and various staircases. The purpose of the article is to draw the geometric dimensions of the main premises of the building, since there is still no complete drawing of the plans